2020
DOI: 10.30519/ahtr.656469
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Meaning in Life in The Relationship Between Memorable Tourism Experiences and Subjective Well-Being

Abstract: Due to varying tourist motivations and needs, involvement in new experiences has different individual consequences. This paper examines the predictive relationship between memorable tourism experience (MTE), meaning in life (MIL) and subjective well-being (SWB). It further investigates whether meaning in life mediates memorable tourism experience's influence on subjective well-being. The study design was cross-sectional, with data collected from 283 tourists visiting Cappadocia, Turkey. Although all variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Emotions are mentioned as one of the essential elements of tourism experiences (e.g., Aydin & Omuris, 2020;Coudounaris & Sthapit, 2017;Gibson et al, 2021;Huang et al, 2020;Lee et al, 2018;Lin et al, 2014;Loureiro et al, 2019;Mendonca-Pedro et al, 2021;Nawijn, 2011;Sie et al, 2021;Sthapit & Coudounaris, 2018;Wang et al, 2021). Nevertheless, this study acknowledges the critical role of adverse emotions in evaluating meaningful experiences since these emotions are equally decisive in explaining the meaning individuals attribute to their experiences.…”
Section: Theoretical Implicationsmentioning
confidence: 79%
See 2 more Smart Citations
“…Emotions are mentioned as one of the essential elements of tourism experiences (e.g., Aydin & Omuris, 2020;Coudounaris & Sthapit, 2017;Gibson et al, 2021;Huang et al, 2020;Lee et al, 2018;Lin et al, 2014;Loureiro et al, 2019;Mendonca-Pedro et al, 2021;Nawijn, 2011;Sie et al, 2021;Sthapit & Coudounaris, 2018;Wang et al, 2021). Nevertheless, this study acknowledges the critical role of adverse emotions in evaluating meaningful experiences since these emotions are equally decisive in explaining the meaning individuals attribute to their experiences.…”
Section: Theoretical Implicationsmentioning
confidence: 79%
“…The Meaning in Life Scale (Steger et al, 2006) was used by Aydin and Omuris (2020) to explore the presence of meaning and the subjective view of experiences (MLQ-P) and the search for meaning (MLQ-S).…”
Section: Assessment Tools and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sthapit et al (2020b) aimed to analyse the components of a negative memorable Airbnb experience. Aydın and Omuris (2020) investigated the predictive relationship between meaning in life, MTE, and subjective well-being. Coelho and Gosling (2018) aimed to develop and test a scale to evaluate MTEs, and they developed an MTE scale consisting of 10 dimensions and 35 items.…”
Section: Memorable Tourism Experiencementioning
confidence: 99%
“…When the academic studies on the quality of experience are examined, it is seen that the researched subjects are, satisfaction (Cole & Scott, 2004), satisfaction and behavioral intention (Cole and Illum, 2006), individuals' personal value judgments about a product or service (Yu & Fang, 2009), performance visitor management (Göktuğ & Yenilmez Arpa, 2015), perceived value and satisfaction, recommendation (Altunel & Günlü, 2015), loyalty and satisfaction (Fernandes and Cruz, 2016), life satisfaction, renewal experience (Yıldız et al, 2019), image of hotel businesses, guests' perception of value and repeating purchase intention (Çetiner & Yaylı, 2020), satisfaction, quality of life (Solunoğlu & Yayla, 2020) and destination image, perceived value (Akkuş & Şimşek, 2021). In the literature review on memorable tourism experiences, it was determined that there are researches in the subjects of feelings (Ruffolo and Servidio, 2016), loyalty behaviors (Kim, 2017), winter tourism (Akkuş, 2017), cultural tourism (Chen & Rahman, 2018), memorable trip (Güçlütürk Baran, 2019), entertainment, advice and revisiting intentions (Chen et al, 2020), customer satisfaction, intention to recommend and revisit intention (Keskin, et al, 2020;Ünal & Bayar, 2020), subjective well-being (Aydın & Ömüriş, 2020), psychological well-being (Karaca & Tağraf, 2021), and intention to revisit (Kahraman & Tanrıverdi, 2021) As a result of the examinations, no study was found in which the quality of experience and the memorable tourism experience were investigated together. In this study, it is aimed to examine the effects of experience quality on memorable tourism experience.…”
Section: Introductionmentioning
confidence: 99%